Peningkatan Prestasi Belajar IPA Melalui Penggunaan Metode Picture And Picture dengan Media Komik Siswa Kelas IV SDI Miftahul Huda Plosokandang Kedungwaru Tulungagung - Abu Zaeni (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Failure in learning is faced on average by several students who do not have the encouragement to learn, and it also results in their learning achievements in science subjects becoming less or below the KKM (Minimum Completion Criteria). The type of research that will be done by researchers is Classroom Active Research (CAR). By using theAction Test picture and picture method with comic media, successfully proved the increase in learning achievement of grade 4 students of SDI Miftahul Huda in science learning.